Redesigning the course “Research Methods in Social and Clinical Pharmacy” - Cantarero-Arévalo, Lourdes (Improving University Science Teaching and Learning, 2023)
The implementation of this assignment is part of the supervision sessions and the development of my teaching portfolio. This assignment is an attempt to redesign the course “Research methods in social and clinical pharmacy” with the intention of making it more aligned and therefore more effective regarding the development on skills and competencies of the students.